Framing The Metaverse in Islamic Worship Education: Republika’s Representation of Virtual Hajj Manasik - Erni Nur Izzati; Adi Nugroho (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2025)
This study aims to analyze how Republika, as an Islamic-based media outlet, frames the phenomenon of virtual hajj training (manasik haji virtual), which represents the intersection between digital technology and religious practice. Using a qualitative approach and the framing analysis model proposed by Robert Entman, this research examines a single news text titled “Merasakan Pengalaman Ibadah Haji dan Umroh secara Virtual” (“Experiencing Hajj and Umrah Worship Virtually”), published on March 6, 2025 (Republika, 2025), as its primary object of analysis. The study focuses on identifying the framing elements, including problem definition, causal interpretation, moral evaluation, and treatment recommendation. Preliminary findings indicate that Republika emphasizes the educational and innovative dimensions of using virtual technology in hajj training, framing the metaverse as a means of modernizing Islamic learning without neglecting spiritual values. These findings highlight how Islamic media play a role in negotiating the boundaries between religious piety and technological advancement within the context of religious education.